Violence against women. Call the facts by your name (La Aljaba. Segunda Época. Revista de Estudios de la Mujer, 2018)
In this article we propose to conceptualize and interpret the different forms of violence that women suffer because they are of the opposite gender to the hegemonic and considered, therefore, weak, heteronomous, irrationals. We believe that feminist theory is continually redefined so we present some new or reinterpreted concepts about the types of violence in which the victim is the woman. Specifically we will refer to domestic violence; violation; prostitution; trafficking in women, femicide / feminicide.
Keywords: women; victims; violence; vulnerability